Probabilistic Review on Overstrength Factor of Concrete Outrigger in 100 Story Building in Jakarta - Nathanael Sutoko - NIM : 25017073, Ega
In general, super tall building has long structural period. In the designing phase, this long structural period affect the magnitude of seismic coefficient on structure. SNI 1726:2012 regulate in the building which has long structural period must use minimum seismic coefficient. However, the minimum seismic coefficient will result in conservative design. Therefore, in this research will use the average of minimum seismic coefficient and original seismic coefficient. Using the average coefficient will result in reducing the earthquake load applied in the structure. Therefore, in this research the reliability of outrigger will be checked using non-linear time history analysis and first order second moment to calculate the safety index (β). In the design phase of 100 story building the load combination is taken from SNI 1727:2013, and the reinforcement design fulfill the criteria of SNI 2847:2013. However, this research will compare the load resistance factor design taken from SNI 1727:2013 to load resistance factor design calculated using the certain value of safety index (β) and average seismic coefficient only for concrete outrigger.